Significance of Polymers with "Allyl" Functionality in Biomedicine: An Emerging Class of Functional Polymers - Mijanur Rahman; Aliaa Ali; Erica Sjöholm; Sebastian Soindinsalo; Carl-Eric Wilén; Kuldeep Kumar Bansal; Jessica M. Rosenholm (MDPI AG, 2022)
In recent years, polymer-based advanced drug delivery and tissue engineering have grown and expanded steadily. At present, most of the polymeric research has focused on improving existing polymers or developing new biomaterials with tunable properties. Polymers with free functional groups offer the diverse characteristics needed for optimal tissue regeneration and controlled drug delivery. Allyl-terminated polymers, characterized by the presence of a double bond, are a unique class of polymers. These polymers allow the insertion of a broad diversity of architectures and functionalities via different chemical reactions. In this review article, we shed light on various synthesis methodologies utilized for generating allyl-terminated polymers, macromonomers, and polymer precursors, as well as their post-synthesis modifications. In addition, the biomedical applications of these polymers reported in the literature, such as targeted and controlled drug delivery, improvement i aqueous solubility and stability of drugs, tissue engineering, and antimicrobial coatings, are summarized.